PODEM OS POÇOS TUBULARES PROFUNDOS PROVOCAR ABALOS SÍSMICOS? CASOS ESTUDADOS NO BRASIL - Yamabe, T. H.; Berrocal, J. (Águas Subterrâneas, 2000)
The seismicity in Nuporanga and Presidente Prudente, in São Paulo State, are the most representative cases of seismic activity induced by groundwater wells in Brazil because they have occurred several times. The seismic activity in Nuporanga began in 1977 soon after a 217 m deep well was drilled. In Presidente Prudente it is observed since 1983 and it is related to an 1800 m deep groundwater well’s exploitation. This well was drilled in 1978. The energy liberation in these two localities has been occurred through a large number of small shocks but also through seismic events of larger magnitudes. Understanding the relation between the hydrological environment alteration and the energy liberation process is useful in order to explain the induced seismicity on the Paraná Basin. Trying to find the reason why seismic activity is induced only in some localities in the Paraná Basin even though the high number of hydroelectric power plants and groundwater wells that exist there, the seismic activity on the basin and the presence of sandstone layers inside the basalt were analyzed. In this work some results are presented.